Levantamento florístico das Micrasterias (Conjugatophyceae, Desmidiaceae) do Pantanal de Poconé, estado de Mato Grosso - Santos, Waléria Finícia de Oliveira Duarte dos (2023)
Knowledge of the state of Mato Grosso algae is still very incipient, since it is based only on 13 papers published along a period of 139 years. Algal studies started in the state by the end of the XIX Century, in 1882, with the document of the presence of Nitella acuminata A. Braun var. subglomerata A.Braun and Chara martiana A.Braun, respectively, at the Paraguai River and Villa Marie (today Cáceres). First mention to the occurrence of desmids in Mato Grosso is due to Schmidle, in 1901, from water samples collected at Cuiabá, Paranatinga, Xingu and Ribeirão Formoso. Followed Borges’s publications dated of 1903 and 1925, however, only after a 60 years period came to public the paper by De-Lamonica-Freire, a doctoral dissertation submitted to the Universidade de São Paulo, from which just the genus Xanthidium was formally published. All following publications were catalogues dating from 1989 and 2018. Investigation aimed at surveying the species, varieties and taxonomic formae of Micrasterias living in water bodies of the Poconé Pantanal. Study area of the present investigation was the Poconé Pantanal, from which 34 sampling units were collected from 17 different localities along the Transpantaneira Road. Plankton material was gathered by horizontal draggings with a 20 μm mesh plankton net at the water body superficial layer (± 30 cm deep), and the periphytic material by squeezing partial or totally submerged macrophytes. All material collected was immediately fixed and preserved with Transeau solution 1:1 with the sample liquid. Exam of the material was performed using a light microscope coupled with a photographic camera. The genus Micrasterias was ereced by C. Agardh, validated by J. Ralfs, and includes basically free living, solitary, unicell representative individuals, but there is one species (M. foliacea) that forms pseudofilaments (filamentous colonies). The cell is most commonly circular or elliptical in outline, with more or less deep incisions delimiting lobes and lobules, and bilateral simmetry at the three orthogonal planes. Exam of the material collected, the material deposited at the Universidade Federal de Mato Grosso herbarium, and that of the specialized Mato Grosso literature allowed identification of 24 Micrasterias taxa, including 15 species, 8 non typical varieties of their respective species, and 2 also non typical taxonomic formae, however, of their respective varieties. They were also identified 2 materials that we concluded to be species that were never described and 1 taxonomic variety equally new, whose description and formal proposition will be done in the near future, since theses and dissertations do not constitute effective publication of scientific names. The species M. pinnatifida, M. rotata, M. sanctipaulensis and M. truncata; the varieties M. arcuata var. arcuata, M. furcata var. croasdaleae, M. laticeps var. ampliata, M. mahabuleshwarensis var. amazonensis, M. radians var. radians, M. radians var. brasiliensis, M. rotata var. rotata f. rotata e M. torreyi var. torreyi; and the taxonomical forma M. rotata var. rotata f. evoluta were identified for the first time for the state of Mato Grosso. Micrasterias abrupta var. abrupta was the most common species among all in the present study, occurring in 8 distinct localities of the Poconé Pantanal, followed by M. borgei var. borgei in 7 localities, and by M. furcata var. croasdaleae in 6 localities. Taxonomic distinction between M. pinnatifida var. pinnatifida and M. arcuata var. arcuata was not easy, since the only difference between them resides on the upper margin of the polar lobe that is slightly retuse at the mid portion in the first species, and strongly retuse in the second species. Present investigation amplified the taxonomic diversity of the genus Micrasterias in about 54.2% for the state of Mato Grosso.